Study on the dependence of alpha-fetoprotein content in human cord blood extracts on extraction conditions - Shcheniavskyi, Ivan; Akhatova, Yuliia; Moisieieva, Natalia; Gorina, Olga; Lipko, Oksana (Problems of Cryobiology and Cryomedicine, 2026)
Probl Cryobiol Cryomed. 2025; 35(4): 224—226